1997
DOI: 10.1007/pl00005688
|View full text |Cite
|
Sign up to set email alerts
|

Learning impairment induced by lesion of the CA1 field of the primate hippocampus: attempts to ameliorate the impairment by transplantation of fetal CA1 tissue

Abstract: Monkeys with bilateral excitotoxic lesion of the CA1 field of the hippocampus were severely impaired at learning visuospatial conditional tasks. This was not a general spatial impairment, because the animals were not impaired on serial spatial reversal, which requires response flexibility in the spatial domain; they were not impaired at learning to choose the position furthest away from a single stimulus, which requires analysis of spatial layout of the test area, and they were not impaired at discriminating b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 53 publications
4
18
0
Order By: Relevance
“…In contrast, studies on the role of the monkey hippocampal formation in spatial learning and memory have resulted in inconsistent results. Although some studies have shown that hippocampal-lesioned monkeys exhibit impaired performance in various spatial memory tasks (Angeli et al, 1993;Beason-Held et al, 1999;Hampton and Murray, 2004;Alvarado and Bachevalier, 2005), others have failed to show any spatial memory impairment (Ridley et al, 1997;Murray and Mishkin, 1998;Malkova and Mishkin, 2003). However, if the monkey hippocampal formation is integrally involved with the processing of spatial relational information, as is the case in rodents, damage to the hippocampal formation should reliably and consistently impair the monkeys' ability to exhibit behavioral strategies dependent on allocentric representations of space.…”
Section: Hippocampal Lesion and Spatial Representationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, studies on the role of the monkey hippocampal formation in spatial learning and memory have resulted in inconsistent results. Although some studies have shown that hippocampal-lesioned monkeys exhibit impaired performance in various spatial memory tasks (Angeli et al, 1993;Beason-Held et al, 1999;Hampton and Murray, 2004;Alvarado and Bachevalier, 2005), others have failed to show any spatial memory impairment (Ridley et al, 1997;Murray and Mishkin, 1998;Malkova and Mishkin, 2003). However, if the monkey hippocampal formation is integrally involved with the processing of spatial relational information, as is the case in rodents, damage to the hippocampal formation should reliably and consistently impair the monkeys' ability to exhibit behavioral strategies dependent on allocentric representations of space.…”
Section: Hippocampal Lesion and Spatial Representationsmentioning
confidence: 99%
“…For example, whereas several studies have demonstrated that hippocampal-lesioned monkeys exhibit impaired performance in various spatial memory tasks (Angeli et al, 1993;Beason-Held et al, 1999;Malkova and Mishkin, 2003;Hampton and Murray, 2004;Alvarado and Bachevalier, 2005), other studies have failed to show any spatial memory impairment after selective hippocampal lesions (Ridley et al, 1997;Murray and Mishkin, 1998;Malkova and Mishkin, 2003). Nevertheless, electrophysiological studies suggest that the primate hippocampus is involved in spatial learning and memory (Rolls et al, 1989;Ono et al, 1991;Rolls and O'Mara, 1995;Georges-Francois et al, 1999;Hori et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…By contrast, the contribution of the nonhuman primate hippocampus to spatial memory has been more difficult to establish. For example, using spatial memory tasks delivered either manually (Wisconsin General Testing Apparatus) or via computer (automated tasks), some studies found spatial memory deficits (Parkinson et al, 1988;Gaffan and Harrison, 1989a,b;Angeli et al, 1993;Gaffan, 1994a,b;Parker and Gaffan, 1997;Beason-Held et al, 1999;Alvarado et al, 2002) but others did not (Ridley et al, 1997;Murray and Mishkin, 1998;Mál-ková and Mishkin, 2003;Belcher et al, 2006). While these discrepant results may reflect whether the hippocampal lesions in these earlier studies encroached or not onto the adjacent parahippocampal areas TH/TF (Málková and Mishkin, 2003;Belcher et al, 2006), three recent studies using selective neurotoxic lesions of the hippocampus have demonstrated severe spatial memory deficits when the animals had to navigate in an environment and forage for food (Hampton et al, 2004;Glavis-Bloom et al, 2006;Lavenex et al, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…Conditional cues therefore have properties similar to occasion setters (Miller & Oberling, 1998). Conditional discrimination learning has been well studied in adulthood in a variety of species including rats (Deacon, Bannerman, & Rawlins, 2001;Good, de Hoz, & Morris, 1998;Murray & Ridley, 1999;Sutherland, McDonald, Hill, & Rudy, 1989;Sziklas & Petrides, 2002;Whishaw & Tomie, 1991), monkeys (Ridley et al, 1997;Ridley, Timothy, Maclean, & Baker, 1995), rabbits (Rogers & Steinmetz, 1998), pigeons (Watanabe, 2002), and in human children (Perez-Gonzalez & Serna, 2003) and adults (Fortier et al, 2003;Serna & Perez-Gonzalez, 2003); however, to our knowledge there have been no studies of conditional discrimination learning in developing rats.…”
mentioning
confidence: 96%